KAJIAN SEMIOTIKA INTERTEKSTUALITAS FILM RALPH BREAKS THE INTERNET - Zulkarnain, Alfiansyah (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
Nowadays, Intertextuality is one of the most important aspect in contemporer film, and deeper research on how intertextuality works in system of signs could produce a theoritical framework in generating narrative as text. This paper will analyze how sign system works on intertextuality through Ralph Breaks the Internet animated film as a study case. The research method used in this paper will be focused on qualitative analysis on teks produced as signs in the film could be read as a recurring semiosis process in certain stages, and how intertextuality could affect its processes. Peirce’s semiosis process schematic will be used as the model. In the end we should be able to identify how and on what aspects intertextuality could influence, develop, and/or shift interpretation of sign in the stages of semiosis processes. The result of the analysis conclude three things: First, intertekstual understanding on texts could enrich the understanding of signs. Second, placement of obligatory intertextual hypertexts (R) could drive audiences to actively try to complete narrative spaces based on hypotexts (O) designed by the writer. Third, the higher the vertical dimensions of text (in which could be observabe through semiosis process stages), the more complex the sign relationship between representamen (sign) and its object (referensi) become. Keywords: intertextuality, semiotics, semiosis, structuralism, Peirce, Wreck-it Ralph, Ralph Breaks the Internet Intertekstualitas hadir sebagai salah satu aspek penting dalam film kontemporer, dan kajian yang lebih mendalam akan bagaimana intertekstualitas bekerja dalam sistem tanda dapat menjadi model kerangka teoritis untuk menghasilkan narasi sebagai teks. Tulisan ini akan menganalisa hal tersebut melalui studi kasus film animasi Ralph Breaks the Internet. Metode penelitian akan terfokus pada kajian kualitatif akan bagaimana teks yang dihasilkan oleh film dapat dibaca dalam tingkatan proses semiosis , dan bagaimana intertekstualitas akan mempengaruhi proses tersebut. Kajian dilakukan berdasarkan landasan teoritis menggunakan skema proses semiosis Peirce sebgai model. Pada akhirnya dapat diidentifikasi bagaimana intertekstualitas mempengaruhi interpretasi tanda pada tingkatan-tingkatan proses semiosis. Hasil analisa menghasilkan tiga hal: Pertama, pemahaman intertekstual mampu memperkaya pembacaan tanda. Kedua, penempatan teks-teks intertekstual wajib dapat membuat audiens secara aktif berusaha turut mengisi ruang-ruang narasi hiperteks (R) berdasarkan hipoteks (O) yang memang sudah dirancang oleh penyaji tanda. Ketiga, semakin tinggi dimensi vertikalitas teks (yang dapat dilihat melalui tingkatan proses semiosis) maka sifat hubungan antara representamen (sign) dan object (referensi) nya semakin kompleks. Kata Kunci: intertekstualitas, semiotika, semiosis, strukturalisme, Peirce, Wreck-it Ralph, Ralph Breaks the Internet